RNA Sequencing of Cardiac in a Rat Model Uncovers Potential Target LncRNA of Diabetic Cardiomyopathy - Xi, Yangbo; Chen, Dongping; Dong, Zhihui; Lam, Hingcheung; He, Jiading; Du, Keyi; Chen, Can; Guo, Jun; Xiao, Jianmin (Frontiers in Genetics, 2022)
Background Diabetic cardiomyopathy (DCM) is one of the major causes of heart failure in diabetic patients; however its pathogenesis remains unclear. Long non-coding RNAs (lncRNAs) are involved in the development of various cardiovascular diseases, but little is known in DCM. Objective The present study aimed to investigate the altered expression signature of lncRNAs and mRNAs by RNA sequencing and uncovers the potential targets of DCM. Methods A DCM rat model was established, and the genome-wide expression profile of cardiac lncRNAs and mRNAs was investigated in the rat model with and without DCM by RNA sequencing. Bioinformatics analysis included the co-expression, competitive endogenous RNAs (ceRNAs) network and functional enrichment analysis of deregulated lncRNAs and mRNAs. Results A total of 355 lncRNAs transcripts and 828 mRNAs transcripts were aberrantly expressed. The ceRNA network showed that lncRNA XR_351927.3, ENSRNOT00000089581, XR_597359.2, XR_591602.2, and XR_001842089.1 are associated with the greatest number of differentially expressed mRNAs and AURKB, MELK, and CDK1 may be the potential regulatory targets of these lncRNAs. Functional analysis showed that these five lncRNAs are closely associated with fibration, cell proliferation and energy metabolism of cardiac myocytes, indicating that these core lncRNAs have a high significance in DCM. Conclusions The present study profiled the DCM-specific lncRNAs and mRNAs, constructed the lncRNA-related ceRNA regulatory network, and identified the potential prognostic biomarkers, which provided new insights into the pathogenesis of DCM.